Consciousness Disturbances Reported With Clindamycin Versus Cefazolin in Surgical Patients: A Global Pharmacovigilance Analysis Using VigiBase - Nishida, Kazuki; Chrétien, Basile; Morioka, Hiroshi; Tamakoshi, Daigo; Hiraga, Keita; Nakamura, Tomoyuki; Matsui, Shigeyuki; Katsuno, Masahisa; Hara, Yoshitaka (Clinical and Translational Science, 2026)
Clindamycin is a common β-lactam substitute for surgical prophylaxis. Whether peri-operative disturbances in consciousness are disproportionately reported with clindamycin in global pharmacovigilance data remains unclear. Using WHO VigiBase (up to January 27, 2025), we performed a de-duplicated case/non-case disproportionality analysis of Individual Case Safety Reports (ICSRs) co-reporting ≥ 1 anesthetic or sedative. Cases were defined by the MedDRA HLT "Disturbances in consciousness NEC." We estimated RORs and aRORs for clindamycin versus cefazolin and other peri-operative comparators (metronidazole, vancomycin, ampicillin), adjusting for age group, sex, and co-reported medications. K-modes clustering characterized co-reporting patterns among clindamycin reports. Sensitivity analyses excluded sepsis-related terms/vasopressors and applied a narrower outcome definition excluding syncope/presyncope. Of 3623 clindamycin ICSRs, 159 (4.4%) included a consciousness-disturbance term. Versus cefazolin, clindamycin generated a disproportionality signal (ROR 2.59, 95% CI 2.07-3.24; aROR 2.23, 95% CI 1.70-2.91), with similar estimates after excluding sepsis/vasopressors (aROR 2.21, 95% CI 1.64-2.98) and syncope/presyncope (aROR 2.11, 95% CI 1.60-2.79). Clustering suggested co-reporting patterns consistent with lidocaine-enriched older-age reports, sedative/anesthetic-enriched younger-age reports, and opioid-enriched reports with high-acuity markers. In VigiBase, disproportionality analyses identified a reporting signal for disturbances in consciousness with clindamycin relative to cefazolin in surgical settings. Because spontaneous reports lack exposure denominators and are susceptible to residual confounding, these findings are hypothesis-generating and do not estimate incidence or comparative risk. Evaluation in data sources with denominators and prospective clinical characterization is warranted.